A Statistical Assessment of Liquidity Management and Profitability in a Cross Section of Deposit Money Banks in Nigeria using Panel Analysis - SHAIBU, Ibrahim; OKAFOR, Chinwuba (Archives of Business Research, 2020)
The objective of this study was to examine the relationship between liquidity and profitability of deposit money banks in Nigeria using panel approach. The study made use of a sample size of ten deposit money banks in Nigeria. Data used for the study were sourced from the annual reports of the sampled firms and the statistical bulletin of the Central Bank of Nigeria ranging from 2006 to 2016. The liquidity indicators that were used were current ratio (current assets to current liabilities) (CRT), cash to total asset ratio (CTA), cash to total deposit ratio (CTD), liquid asset to total assets ratio (LATA), and loan to total deposit ratio (LTD), while return on assets (ROA) was used as proxy for profitability. A panel data regression model was specified and estimated. The empirical results showed that there was a positive and statistically significant relationship between cash to total asset (CTA) ratio and liquid asset to total assets (LATA) with profitability, and there was a negative but statistically significant relationship between cash to total deposit (CTD) ratio and profitability. It was also revealed that current ratio (CRT) and loan to total deposit (LTD) had a positive but statistically not significant relationship with profitability. It was recommended that the deposit money banks should not only focus on the profit maximization perception but also embrace methods that will certify effective and efficient liquidity management since its survival and sustainability depends on effective liquidity management and profitability. This will help to reduce the negative effects of the incidence of deficient and excessive liquidity.